Fostering science and technology management human resource in Vietnam according to competency-based approach - Huy, Tran Quang; Giang, Tu Thao Huong; Tung, Chu Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
There are several approaches in training science and technology management human resource development, of which competency-based training is widely applied in developed countries with some advantages in comparison with traditional training approaches. Based on theory of human resource development, international experiences and empirical research, this article proposes competency-based training for managerial human resource in the Ministry of Science and Technology (MOST). This application will promote managers’ competencies to ensure the improvement of state management in science and technology of MOST in the coming years. Code: <em style="color: #000000; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: italic; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">20071701